Neutrophil Extracellular Traps, Sepsis and COVID-19 – A Tripod Stand - Ventura-Santana, Esmeiry; Ninan, Joshua R.; Snyder, Caitlin M.; Okeke, Emeka B. (Frontiers in Immunology, 2022)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current coronavirus disease 2019 (COVID-19) pandemic. Majority of COVID-19 patients have mild disease but about 20% of COVID-19 patients progress to severe disease. These patients end up in the intensive care unit (ICU) with clinical manifestations of acute respiratory distress syndrome (ARDS) and sepsis. The formation of neutrophil extracellular traps (NETs) has also been associated with severe COVID-19. Understanding of the immunopathology of COVID-19 is critical for the development of effective therapeutics. In this article, we discuss evidence indicating that severe COVID-19 has clinical presentations consistent with the definitions of viral sepsis. We highlight the role of neutrophils and NETs formation in the pathogenesis of severe COVID-19. Finally, we highlight the potential of therapies inhibiting NETs formation for the treatment of COVID-19.